2022
DOI: 10.15184/aqy.2022.138
|View full text |Cite
|
Sign up to set email alerts
|

Water and soil management strategies and the introduction of wheat and barley to northern China: an isotopic analysis of cultivation on the Loess Plateau

Abstract: Studies of ‘food globalisation’ have traced the dispersal of cereals across prehistoric Eurasia. The degree to which these crops were accompanied by knowledge of soil and water preparation is less well known, however. The authors use stable isotope and archaeobotanical analyses to trace long-term trends in cultivation practices on the Loess Plateau (6000 BC–AD 1900). The results indicate that ancient farmers cultivated grains originating in South-west Asia and used distinct strategies for different species. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…To reduce sampling error (houses vs. ash pits), we compared the Lower Changshan data with all data derived from various Qijia residential contexts in the Western Loess Plateau. We found that the weed proportion of ash pits derived from other Qijia sites was 9%-16.8% (Yang, 2014;Li, 2018;Li et al, 2022b), which is closer to the Qijia result of this study (12.28%). It suggests that results from different residential contexts (houses vs. ash pits) may not be influenced in this case.…”
Section: Human Planting Strategies In the Midlower Hulu River Valley ...supporting
confidence: 78%
See 4 more Smart Citations
“…To reduce sampling error (houses vs. ash pits), we compared the Lower Changshan data with all data derived from various Qijia residential contexts in the Western Loess Plateau. We found that the weed proportion of ash pits derived from other Qijia sites was 9%-16.8% (Yang, 2014;Li, 2018;Li et al, 2022b), which is closer to the Qijia result of this study (12.28%). It suggests that results from different residential contexts (houses vs. ash pits) may not be influenced in this case.…”
Section: Human Planting Strategies In the Midlower Hulu River Valley ...supporting
confidence: 78%
“…The significance of foxtail millet in plant subsistence strategy was slightly higher in the Qijia period than in the Lower Changshan period. The increased weight of foxtail millet relative to broomcorn millet as a cropping strategy in the MLHRV during the Qijia period in comparison to the Banpo-Miaodigou period (~6,100-5,500 BP) and the late Yangshao period (~5,500-4,800 BP) were reported in previous archaeobotanical studies (Li et al, 2022b;Yang Y et al, 2022). Our results from the ZTXFC site are the first reported archaeobotanical data of the Lower Changshan culture.…”
Section: Human Planting Strategies In the Midlower Hulu River Valley ...supporting
confidence: 76%
See 3 more Smart Citations